Answer: The solution of the given equation is [tex]\frac{1}{4}[/tex].
Explanation:
The given equation is,
[tex]\frac{2}{3}x^{ -\frac{5}{3}} +\frac{8}{3}x^{ -\frac{2}{3}}=0[/tex]
It can be written as,
[tex]\frac{2}{3x^{ \frac{5}{3}}} +\frac{8}{3x^{ \frac{2}{3}}}=0[/tex]
[tex]\frac{8x^{\frac{5}{3}}-2x^{\frac{2}{3}}}{3x^{\frac{7}{3}}}=0[/tex]
[tex]8x^{\frac{5}{3}}-2x^{\frac{2}{3}}=0[/tex]
[tex]2x^{\frac{2}{3}}(4x-1)=0[/tex]
Equate each factor equal to 0. Then we get,
[tex]x=0[/tex] and [tex]\frac{1}{4}[/tex]
Since the power of x is in negative, so the equation is not defined for x = 0.
Therefore the only solution of the given equation is [tex]\frac{1}{4}[/tex].